Irreversible electroporation of the pancreas is feasible and safe in a porcine survival model - Fritz, Stefan; Sommer, Christof-Matthias; Vollherbst, Dominik; Longerich, Thomas; Sachsenmaier, Milena; Knapp, Jürgen; Radeleff, Boris; Werner, Jens (Pancreas, 2015)
Objectives - Use of thermal tumor ablation in the pancreatic parenchyma is limited because of the risk of pancreatitis, pancreatic fistula, or hemorrhage. This study aimed to evaluate the feasibility and safety of irreversible electroporation (IRE) in a porcine model. - Methods - Ten pigs were divided into 2 study groups. In the first group, animals received IRE of the pancreatic tail and were killed after 60 minutes. In the second group, animals received IRE at the head of the pancreas and were followed up for 7 days. Clinical parameters, computed tomography imaging, laboratory results, and histology were obtained. - Results - All animals survived IRE ablation, and no cardiac adverse effects were noted. Sixty minutes after IRE, a hypodense lesion on computed tomography imaging indicated the ablation zone. None of the animals developed clinical signs of acute pancreatitis. Only small amounts of ascites fluid, with a transient increase in amylase and lipase levels, were observed, indicating that no pancreatic fistula occurred. - Conclusions - This porcine model shows that IRE is feasible and safe in the pancreatic parenchyma. Computed tomography imaging reveals significant changes at 60 minutes after IRE and therefore might serve as an early indicator of therapeutic success. Clinical studies are needed to evaluate the efficacy of IRE in pancreatic cancer.
Gesehen am 26.06.2020
Im Artikel wurde der Name "Sachsenmaier" fälschlicherweise "Sachsenmeier" geschrieben